Esterification and Transesterification Optimization Processes of Nonedible (Castor and Neem) Oils for the Production of Biodiesel - Hamid Ayyub; Muhammad Arslan; Muhammad Jamshaid; Akbar Ali Qureshi; Arslan Ahmed; Haji Hassan Masjuki; Md. Abul Kalam; Farah Binti Ahmad; Hafiz Liaqat Ali; Muhammad Umair Ahsan Khan; Muhammad Umer Khallidoon (Fuels)
In current times, the diminishing reserves of petroleum, increased energy consumption across various sectors, and their consequential environmental impact have become apparent. Consequently, it is necessary to develop sustainable and eco-friendly energy sources to meet growing demands. The article aimed to blend castor and neem oils (in a 50:50 ratio) to rectify the drawbacks present in castor biodiesel such as elevated kinematic viscosity and density. Response surface methodology was used to study the optimization of the two-step biodiesel production process through the use of a central composite design (CCD). For the esterification step, a methanol-to-oil molar ratio of 7.5:1, 1.75 wt.% of H2SO4, and a temperature of 55 °C were optimal. In the transesterification step, optimized conditions included a methanol-to-oil molar ratio of 9:1, 2.50 wt.% of calcium oxide, a temperature of 55 °C, and a stirring speed of 900 rpm, resulting in a 93% yield of methyl ester. Different properties of produced biodiesel were examined using the standard values provided by EN 14214 and ASTM D6751. The production of biodiesel from a mixture of castor and neem oils did not have any adverse impacts on food security.